New Answers to Old Questions - Kanjooparampil, Theophane (Journal of Dharma, 1976)
A great controversy within the Catholic Church had raged for the past three hundred years on the subject of predestination: whether God decrees to save or not to save a certain man after look- ing at his merits or demerits. After carefully studying the views of different schools the author has offered a solution which, according to him, is liked by many modern theologians. In brief, the solution in the words of the author himself will be as follows: There are three theological stages in the process of predestination: 1. The Universal salvific will of God which is sincere and extremely strong; 2. The reprobation of all whom God foresees will gravely and persistently resist grace. Reprobation is after, and because of, foreseen demerits. 3. Predestination of all others, in whom God does not foresee grave and persistent resistance